Analisis Pengaruh Kepuasan Kerja dan Stres Kerja Terhadap Kinerja Dimediasi oleh Organizatonal Citizenship Behavior (OCB) pada Karyawan Bank Jatim Cabang Pacitan - Murjoko Teguh Hariyanto; Dwi Orbaningsih; Ahmad Ahmad (Universitas Batanghari Jambi, 2023)
The aim of study aimed to analyze the influence of job satisfaction and job stress on performance mediated by organizational citizenship behavior (OCB) on Bank Jatim Pacitan branch employees. The method used in this study is quantitative, emphasizing its analysis of numerical data (numbers) processed by statistical methods. Data in the form of numbers in this study were obtained from the results of filling out questionnaires, namely surveys conducted by collecting information using questionnaires by distributing questionnaires, tests, structured interviews, and so on. Based on the processing of the variable test shows that job satisfaction has a positive effect on OCB and employee performance. Job stress variable hurts OCB and employee performance. And the OCB variable can mediate this research so that it produces significant results. This shows that the employees of the Pacitan Branch of Bank Jatim have good employee performance and a supportive environment. Thus, forming OCB. The attitude of mutual help among employees is very strong so that the target of the Pacitan Branch of the Bank Jatim company is achieved. Following the conditions in the field, the target of the Bank Jatim Pacitan Branch was achieved by more than 100%. This research contributes to improving the performance of company employees and offers solutions that can be used to increase employee productivity.